Front cover & preliminary pages (Journal of Irish Urban Studies, Vol.1 (No. 1), 2002 - (:unkn) unknown (Centre for Urban and Regional Studies. Trinity College Dublin, & the Faculty of the Built Environment, Dublin Institute of Technology. Bolton Street, 2002)
The publication of the Journal of Irish Urban Studies marks a growing recognition of the importance of urban-related issues in Irish society. It has been establlshcd as a forum for the dissemination of researeh and the stimulation of discussion and debate. I! is ajoint initiative of the Centre for Urban and Regional Studies. Trinity College Dublin, and the Faculty of the Built Environment, Dublin Institute of Technology. Bolton Street.
Keywords: Urban geography -- Ireland